Two-week supplementation of Bifidobacterium adolescentis iVS-1 reduces symptoms associated with lactose intolerance in lactose maldigesters - Monica Ramakrishnan; Tzu-Wen L. Cross; Anna Clapp Organski; Sindusha Mysore Saiprasad; Abigayle M. R. Simpson; Daniel J. Tancredi; Mallory J. Van Haute; Chloe M. Christensen; Zachery T. Lewis; Thomas A. Auchtung; Jens Walter; Robert Hutkins; et al. (Gut Microbes Reports)
Probiotic supplements containing high β-galactosidase-producing bacteria may aid in the management of lactose intolerance. We previously isolated a strain of Bifidobacterium adolescentis, iVS-1, from the fecal sample of a human donor after consumption of galactooligosaccharides (GOS), a prebiotic derived from lactose. Therefore, it was hypothesized that iVS-1 might reduce symptoms associated with lactose maldigestion. Compared to other probiotic strains, iVS-1 had high β-galactosidase activity and reduced gas formation by fecal communities during in vitro fermentations of lactose or milk. A randomized placebo-controlled clinical trial was then conducted with 21 lactose maldigesters, randomized to receive either B. adolescentis iVS-1 (n = 11) or placebo (n = 10) daily for 2 weeks. Compared to the two-week run-in period, iVS-1 abundance was higher both at the end of the treatment period (p = 0.0005) and after the 2-week post-treatment period (p = 0.045). The iVS-1 group reported less overall daily symptoms during the treatment period when compared to placebo (p = 0.032) and had significant improvement for fecal urgency (p = 0.033) and diarrhea (p = 0.006). The metabolism of lactose, reduction of gas, and improvement of multiple gastrointestinal symptoms suggest that B. adolescentis iVS-1 may be an effective treatment for lactose intolerance.Trial Registration: The trial is registered at ClinicalTrials.gov (https://clinicaltrials.gov/study/NCT05668468).